Efficacy of Sauropus androgynous Leaves Extract Gel on Burn Wound Healing in Albino Rats - Panggabean, Rosenna Tiara; Sudjarwo, Sri Agus; Ma'ruf, Anwar; Widiyatno, Thomas Valentinus; Yudaniayanti, Ira Sari; Kurnijasanti, Rochmah; Khairullah, Aswin Rafif (Jurnal Medik Veteriner, 2023)
Burns not only damage skin locally but generally affect the body system and have been related as the secondary cause of death. Burns can be effectively treated with a topical drug to prevent chronic inflammation. Burn wound healing is really important for ensuring overall health and well-being. This study aimed to determine the effect of Sauropus androgynous leaves extract gel on the number of fibroblasts, fibrocytes, and collagen density on burn wound healing in albino rats. A total of 50 male albino rats were randomly divided into five groups i.e. (C-) was normal skin, (C+) was skin burn treated with placebo, (T1) was skin burn treated with 2.5% of S. androgynous leaves extract gel, (T2) was skin burn treated with 5% of S. androgynous leaves extract gel, and (T3) was skin burn treated with 10% of S. androgynous leaves extract the gel. The amount of 25 albino rats' skin samples were collected on the 8th day, and the remaining samples were collected on the 15th day. The results showed that 10% of S. androgynous leaves extract gel improved faster, as indicated by the increased number of fibroblasts, fibrocytes, and collagen density. This study can be concluded that 10% of S. androgynous leaves extract gel was the effective dosage to increase the number of fibroblasts, fibrocytes, and collagen density in burn wound healing.